1992
DOI: 10.1029/90ja02356
|View full text |Cite
|
Sign up to set email alerts
|

Electric field observations of equatorial bubbles

Abstract: We present here results from the double floating probe experiment carried on the San Marco D satellite, with emphasis on the observation of large incremental changes in the convective electric field vector at the boundary of equatorial plasma bubbles. This study concentrates on isolated bubble structures in the upper ionospheric F region and divides these observed bubble encounters into two types, type I (live bubbles) and type II (dead bubbles). Type I bubbles show varying degrees of plasma density depletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 19 publications
6
38
0
Order By: Relevance
“…Hanson and Bamgboye, 1984]. More recent studies of bubble plasma dynamics by Aggson et al [1992] have shown that bubble plasma may indeed rise vertically and be well correlated with the overall density variations, but the bubble plasma may later stagnate and even on occasions be seen to move downward. It may therefore be appropriate to consider bubble A in terms of a stagnated bubble, where the large-scale plasma drift inside the depletion is very small.…”
Section: Discussionmentioning
confidence: 99%
“…Hanson and Bamgboye, 1984]. More recent studies of bubble plasma dynamics by Aggson et al [1992] have shown that bubble plasma may indeed rise vertically and be well correlated with the overall density variations, but the bubble plasma may later stagnate and even on occasions be seen to move downward. It may therefore be appropriate to consider bubble A in terms of a stagnated bubble, where the large-scale plasma drift inside the depletion is very small.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, they diffuse down the magnetic field lines to lower altitudes at low latitudes. The plasma inside the depletions has been found to have velocities both perpendicular and parallel to the geomagnetic field (Hanson and Bamgboye, 1984;Aggson et al, 1992). The post-sunset equatorial F layer can become unstable under the influence of any disturbance produced by gravity waves, neutral winds or some other source and can generate plasma irregularities through Rayleigh-Taylor instability (RTI) (Hysell et al, 1990;Singh et al, 1997a).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, vector electric fields in the frequency range f from 10 to 500 Hz have been measured on the 400 km altitude polar orbiting OV1-17 satellite (Kelley andMozer, 1972), andHoltet et al (1977) demonstrated the association between spread-F properties and electrostatic noise near lower hybrid frequency (f LH R ∼10-15 kHz). Recently, Aggson et al (1996) presented electric field data from the San Marco D spacecraft in terms of structure and dynamics of ionospheric plasma (between 500 km and 800 km) depletions associated with night side equatorial spread-F. They measured two DC electric field components in the zonal flow, westward and eastward, and found bifurcations of these depletions.…”
Section: Introductionmentioning
confidence: 99%